2003
DOI: 10.1111/1540-5885.2002003
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Environmental Turbulence on New Product Development Strategy Planning

Abstract: Managers need guidance on how to cope with turbulent environments in order to improve corporate performance. Research on environmental turbulence has suggested that firms adopt a less centralized, more organic structure in dynamic, uncertain environments. Little work has been done specifically, however, on how environmental turbulence affects strategy planning for new product development (NPD). In this article, we specify a baseline model with firm innovativeness, market orientation and top management risk tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
437
2
18

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 527 publications
(485 citation statements)
references
References 63 publications
12
437
2
18
Order By: Relevance
“…We selected the two-group methodology because Ahire et al (2000), Calantone et al (2003), and Koufteros et al (2006) demonstrated in similar studies that this device is more appropriate to evaluate moderator effect compared to an approach in which environmental effects are posited as direct effects. Appendix A presents a six-stage procedure proposed by Hair et al (2010) for conducting a multi-group analysis.…”
Section: Model Analysismentioning
confidence: 99%
“…We selected the two-group methodology because Ahire et al (2000), Calantone et al (2003), and Koufteros et al (2006) demonstrated in similar studies that this device is more appropriate to evaluate moderator effect compared to an approach in which environmental effects are posited as direct effects. Appendix A presents a six-stage procedure proposed by Hair et al (2010) for conducting a multi-group analysis.…”
Section: Model Analysismentioning
confidence: 99%
“…In the contrast, Calantone et al (2003) reached, in the study under title "The Effect of Environmental Turbulence on New Product Development Strategy planning", that the environmental turbulence with its elements affects the new product development strategy planning in four different industries in the united states of America.…”
Section: Competitive Intensitymentioning
confidence: 98%
“…MacCormack and Verganti (2003) described the ET as an anatomical description of the responding process to the environmental changes in a flexible form, while Calantone, Garcia, and Dröge (2003) showed that ET is the uncertainty state residing in the environment and the threats/risks that it is possible to be encountered by the businesses organization. Pavlou and El Sawy (2006) stressed that ET represents a common scale for change and prediction in the environment in which the works organization operates.…”
Section: Environmental Turbulencementioning
confidence: 99%
“…this procedure has been frequently used in various studies (Calantone, Garcia, & Dröge, 2003;Coote, Forrest, & tam, 2006;Dayan & Di Benedetto, 2010) and the steps taken to check for moderator effects are as follows. First, the items of each moderator constructs (mobility context, physical context, and social context) were summed to create a composite scale.…”
Section: Multigroup Analysismentioning
confidence: 99%